Consumer research and service staff involvement in the service development process : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Product Development at Massey University, New Zealand - Shekar, Aruna (Massey University, 2003)
The purpose of this research was to apply consumer research techniques to the development of services. The study also developed ways for involving both the consumer and service staff in the first stage of Service Development. A new model for the first stage of Service Development was proposed and tested. One of the first of its kind in the public domain in New Zealand, this study presents an empirical evaluation of the application of consumer research techniques to local government Service Development. Four Service Development case studies were conducted with the Palmerston North City Council, New Zealand. The research focused on the first stage of Service Development and therefore much of it was oriented towards methods and techniques for eliciting, transforming and representing consumer requirements for the development of services. The model included the sub-stages of service development strategy, opportunity identification, needs analyses, service idea generation and screening, detailed investigation, service concept development and evaluation. The nature of a service product being a result of the interaction between the service staff and consumers required that Service Development involve these two key groups. Consumer research techniques were selected and applied based on the results of the literature review, the research objectives, the nature of services and the outcomes desired. Methods for involving both service staff and consumers in the process of early Service Development were examined and the new model was tested empirically. The main consumer research techniques included mail surveys, telephone interviews, personal interviews, self-administered surveys and focus groups. The new technique of joint focus groups with service staff and consumers was trialled. As part of the focus groups, some idea generation techniques such as word-storming, postbox technique, brainstorming and role-playing were tested with consumers, and where appropriate with service staff. Some of the traditional consumer research techniques used in Product Development needed to be modified slightly to accommodate the intangibility of services. For example, stimulus material such as word lists, video clips and visual collages were provided to respondents as tangible references to stimulate idea generation. Consumer techniques that allowed for the exploration of the interaction between service staff and consumers, and those that permitted the presentation of tangible stimuli were found to be more useful. Analysis tools such as the Quadrant analysis and Perceptual Mapping techniques were used successfully to represent consumer attitudes and perceptions towards the services that were studied. Segmentation of consumers based on consumer attitudes towards the specific service are recommended rather than only demographic segmentation. Matrices were developed to systematically and rationally move from one sub-stage to the next. A Service Development framework that incorporates the participation of consumers and service staff in the Service Development process was created based on the literature and the service context. This model was applied and tested in the four case studies with a local government in New Zealand, to produce the final NuServ model for Service Development. The extent of involvement of service staff in service delivery varies and therefore a range of services was selected within the local government, where a real opportunity or need for service improvement or development existed. A key message that emerged from the research is that Service Development benefits from the participation of both consumers and service staff. Service developers should adopt the consumer research techniques for a more participatory process of development. The Service Development model provides a process guide to service managers for developing and improving services. This research also provided insights and new directions for future studies in Service Development.
Keywords: Service development; Consumer research; Local government service; Palmerston North City Council staff; Service staff